IDENTIFIKASI KEMAMPUAN BERTANYA DAN BERPENDAPAT CALON GURU BIOLOGI PADA MATA KULIAH FISIOLOGI HEWAN - Muh. Amin Astuti (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2017)
The ability of asking and opining can be used to measure students critical thinking skills. The purpose of this study was to determine the students’ ability of asking and opining at learning program of preservice biology teachers. This type of research was a survey with a qualitative descriptive approach conducted in the subject of Animal Physiology. The research was conducted in the academic year 2015/2016. The research subjects consisted of 109 students in STKIP Indonesia Makassar, UIN Alauddin Makassar, UPRI Makassar. The research instrument was observation sheet related to the students’ ability of asking and opining. The data analysis related to the question quality of students showed that 76.92% questions are classified of Lower Order Thinking Skills (LOTS) and 23.08% questions are classified of Higher Order Thinking Skills (HOTS). The data analysis results related to the students ability of opining showed that 86.66% opinions are classified as Lower Order Thinking Skills (LOTS) and 13.34% opinions are classified as Higher Order Thinking Skills (HOTS). These results suggest that the students’ ability to ask and to opine are not fully empowered yet in the learning process, so those abilities still need to be improved. Keywords: Asking Ability, Higher Order Thinking Skills, Lower Order Thinking Skills, Opining Ability